The Effect of HCL Concentration on Gelatin Yield, Moisture, and ASH Content from Rabbit’s (Lepus Nigri Collis) Skin - Gumilar, Jajang; Himina, Ashafa Maida; Suryaningsih, Lilis (International Journal of Scientific Research and Management (IJSRM), 2024)
Rabbits are slaughtered to get meat, while local rabbit skins are not used because the quality of the skin is poor, therefore local rabbit skins become waste. Rabbit skin contains collagen which is a potential source of gelatin.  Gelatin can be obtained from the denaturation of collagen in rabbit skin.  HCl is a strong acid with many hydrogen ions so it can hydrolyze collagen fibers into gelatin.  This research aimed to examine the influence of HCl concentrations on yield,  moisture content, and ash content in gelatin from rabbit skin. This study uses an experimental method with a Completely Randomized Design followed by Tukey’s test.  There were five concentrations of HCl (T1=1%, T2=2%, T3=3%, T4=4% and T5=5%) with three replications.  Statistical analysis showed that HCl treatment had a significant effect (P